Study of wakefields in longitudinally and transversely inhomogeneous rectangular dielectric resonators - Markov, P.I.; Kiselev, V.A.; Kniaziev, R.R.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2014)
At Institute of Plasma Electronics and New Methods of the Acceleration of NSC KIPT the experimental inspection of the principles of creation of multi-bunch and the multimode wakefield dielectric accelerator is carried out. For clearing up of the physical processes arising in case of excitation the wakefield and dynamics of electron bunches in such accelerator we executed a series of analytical and numerical calculations, and also full three-dimensional simulation by means of the developed 3D code is carried out. Wakefields were excited in case of injection of sequence of electron bunches in a rectangular vacuum wave guide of R32 type (72.14 ×34.04 mm) or R26 type (86.36 ×43.18 mm), filled with dielectric with the relative dielectric permittivity ε = 3.8, covering two opposite wide walls of a waveguide. The bunch repetition frequency was 2,805 GHz, energy of electrons was 4.5 MeV, average current was 0.73 A and a charge of one bunch was 0.26 nC. The electron bunches arriving through an open input end of a dielectric waveguide were deviated by a cross magnetic field of permanent magnets to a metal wall of waveguide free of dielectric. Depending on the location of magnets along a structure axis the length of interaction of electron bunches with a dielectric waveguide varied. Experimentally the linear dependence of the electric field value excited by bunches, near an output end of a semi-limited dielectric waveguide versus the interaction length is found. The 3D modeling executed by us researched possibility of the growing dependence of amplitude of a longitudinal electric field found in experiment at an output end of a waveguide from interaction length. The chronology of longi-tudinal electric field near output end on axis of system was probed and it spectral characteristic were analyzed too. The carried out researches allowed to better understanding the physical processes happening in the wakefield dielectric accelerator.